2009
DOI: 10.1088/0022-3727/42/20/205303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of surface nanostructures on rutile (TiO2): comparative study of low-energy cluster ion and high-energy monoatomic ion impact

Abstract: The formation of nanostructures on rutile (TiO2) surfaces formed after the implantation of kiloelectronvolt-energy cluster ions and megaelectronvolt- to gigaelectronvolt-energy multiply charged heavy ions (Iq+, Taq+ and Uq+) is studied. Despite the differences in stopping and energy transfer mechanisms between the kiloelectronvolt-energy cluster ions and megaelectronvolt-energy monoatomic ions, their impacts lead to a similar type of surface damage, namely craters. For the cluster ion implantation the crater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Similar values for the threshold for ion tracks in the bulk and on the surface have often been observed [17,36,37], thus enabling to analyse the threshold with two complementary techniques. SHI irradiation under grazing incidence angles increases the nearsurface interaction volume and therefore induces even more dramatic changes on the material surface.…”
Section: Materials Response To Energetic Ionsmentioning
confidence: 54%
“…Similar values for the threshold for ion tracks in the bulk and on the surface have often been observed [17,36,37], thus enabling to analyse the threshold with two complementary techniques. SHI irradiation under grazing incidence angles increases the nearsurface interaction volume and therefore induces even more dramatic changes on the material surface.…”
Section: Materials Response To Energetic Ionsmentioning
confidence: 54%
“…1 b) to describe the different zones of the patterned substrate. The depth of the micro-wells (or etching depth) resulting after the localized SHI irradiation and subsequent HF etching, is related to the ion energy and fluence, in addition to the fact that there is a certain chemical etching threshold for rutile TiO 2 [24][25][26][27][28]32]. For the present applied ion energy and fluence a characteristic depth of 2 µm is obtained [28], which is the maximum depth obtainable with the used ion.…”
Section: The Ion-beam Lithography Processmentioning
confidence: 80%
“…Other authors proposed a different mechanism for rough amorphous TiO 2 films that consists of the generation of a Ti-O dangling bond on the TiO 2 surface [40]. The generation of Ti 3+ -O vacancy complexes [41] and the absorption of water or hydroxyl groups [32], due to the induced defects after ion irradiation of rutile single crystals, have also been reported. Finally, it has also been observed that the wettability of smooth hydrophilic surfaces improves by roughening them [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. Prior to this report, surface hillocks were characterized mainly by AFM . This technique has a disadvantage due to artefacts induced by the physical size of the tip and is not capable of discerning between crystalline and amorphous hillocks.…”
Section: Introductionmentioning
confidence: 99%